Чума раків та мармурові раки – нові загрози епізоотичного благополуччя та біобезпеки водойм України - Кулішенко, Олег Миколайович; Kulishenko, Oleg; Kulishenko, O.; Kulishenko, O. М.; Давиденко, Павло Олександрович; Davydenko, Pavel; Davydenko, Pavlo; Davydenko, P. O.; Davydenko, P.; Боровик, Ірина Володимирівна; Borovic, Irina; Borovik, Irina; et al. (Дніпровський ДАЕУ, 2024)
Чума раків (Pestis astacorum, Krebs pest) – це пошесне мікозне захворювання прісноводних раків, яке спричинюється грибком Aphanomyces astaci та проявляється масовим ураженням хітинового покриву панцира раків та їх масовою загибеллю. Захворювання було вперше зареєстроване у Європі (Італія Ломбардія) у 1860-1865 рр куди були завезені раки переносни- ки збудника із США. Хвороба набула значного поширення у ряді країн Європи у 1870-1890-хх і до початку ХХ століття досягла території сучасної України. Чума раків супроводжується надзвичайно високими економічними збитками, що зумовлюють масове захворювання та вимирання прісноводних раків водойм України. В першу чергу Astacus fluviatilis – річкового рака, Astacus leptodactylus – довгопалого рака, Astacus astacus – широкопалого рака. Летальність серед раків може сягати 100 %. Мармуровий рак (Procambarus fallax f. virginalis) – дуже небезпечний інтродуцент водойм України, який має ряд унікальних біологічних властивотей, які більше ніде не зустрічаються у природі. Ці раки всі від народження поліплоїдні самки та розмножуються без запліднення, що дозволяє їм швидко колонізувати водні біоресурси України та витісняти місцеві види. Крім того мармурові раки є переносниками збудника чуми раків, що додатково погіршує епізоотичну ситуацію серед місцевих аборигенних видів раків. Колонії цього рака були вперше виявлені у 2015-2016 рр у озері Котлован у місті Дніпро. Пізніше зареєстровані у водоймах Одеської, Сумської областей. Ряд авторів повідомляє про поширення цих карантинних гідробіонтів у водоймах Словаччини, Бельгії та ряду країн Європи. Crayfish plague (Pestis astacorum, Krebs plague) is a widespread mycotic disease of freshwater crayfish, which is caused by the fungus Aphanomyces astaci and is manifested by a massive lesion of the chitinous cover of the crayfish shell and their mass death. The disease was first registered in Europe (Italy Lombardy) in 1860-1865, where crayfish carrying the pathogen were imported from the USA. The disease became widespread in a number of European countries in the 1870-1890s and by the beginning of the 20th century reached the territory of modern Ukraine. Crayfish plague is accompanied by extremely high economic losses, which cause a mass disease and extinction of freshwater crayfish in Ukrainian reservoirs. First of all, Astacus fluviatilis - river crayfish, Astacus leptodactylus - longfingered crayfish, Astacus astacus - broadfingered crayfish. Mortality among crayfish can reach 100%. The marble crayfish (Procambarus fallax f. virginalis) is a very dangerous introduced species to Ukrainian water bodies, which has a number of unique biological properties that are not found anywhere else in nature. These crayfish are all polyploid females from birth and reproduce without fertilization, which allows them to quickly colonize the aquatic bioresources of Ukraine and displace local species. In addition, marble crayfish are carriers of the crayfish plague pathogen, which further worsens the epizootic situation among local aboriginal crayfish species. Colonies of this crayfish were first discovered in 2015-2016 in Lake Kotlovan in the city of Dnipro. Later, they were registered in water bodies in Odessa and Sumy regions. A number of authors report on the distribution of these quarantine aquatic organisms in the waters of Slovakia, Belgium, and a number of European countries.
Crayfish plague and marble crayfish – new threats to epizootic well-being and biosecurity of Ukrainian water bodies
Кулішенко Олег Миколайович https://orcid.org/0000-0001-6801-2380 Давиденко Павло Олександрович https://orcid.org/0000-0002-8425-3835 Боровик Ірина Володимирівна https://orcid.org/0000-0001-5958-8396
Keywords: епізоотична ситуація; epizootic situation; чума раків; crayfish plague; мармурові раки; marmurovi raky